Digital Payment Adoption in Rural Area - Tsuraya Choirinnida, Irma; Utari, Diah (Universitas muhammadiyah malang, 2025)
This study investigates the implementation and adoption of QRIS (Quick Response Code Indonesian Standard) digital payment systems in rural Indonesia, focusing on factors influencing adoption and its impact on financial inclusion and economic development. Employing a quantitative descriptive approach, data were collected through structured questionnaires from 502 rural QRIS users, selected via purposive sampling. Two-Way ANOVA was used to analyze regional-specific factors affecting adoption patterns in rural contexts. The findings reveal low financial literacy, strong reliance on cash transactions, and limited perceived usefulness of QRIS among rural communities. While basic infrastructure like device ownership and internet access exists to some extent, barriers such as lack of education, limited social support, and low trust in digital financial systems hinder fintech adoption. However, the study identifies growing potential for QRIS usage in rural areas, with user intention indicating a positive outlook, particularly if supported by targeted education, stronger government initiatives, and simplified technology design. This research contributes to the literature on rural fintech adoption by specifically examining QRIS usage in Indonesian villages. It highlights unique barriers such as low financial literacy, limited social support, and trust issues, offering a rural-specific perspective using an integrated analytical framework. Unlike previous studies centered on urban areas, this research provides valuable insights into the challenges and opportunities for digital payment adoption in rural Indonesia. The findings can inform policymakers, fintech companies, and financial institutions in developing strategies to enhance QRIS adoption and promote financial inclusion in rural areas.